2020
DOI: 10.1590/1678-4499.20190153
|View full text |Cite
|
Sign up to set email alerts
|

Silicon nutrition counteracts salt-induced damage associated with changes in biochemical responses in apple

Abstract: Salt stress is an environmental challenge that adversely influences plant responses. Silicon (Si) nutrition plays critical roles in plant tolerance to salt stress. Apple (Malus domestica Borkh.), a salt sensitive fruit species, was used in the present experiment to investigate the influences of Si on salt stress as well as on alterations of biochemical responses. Apple cv Fuji grafted on M9 clonal rootstock was exposed to salt stress for 4 months with 35 mmol•L-1 NaCl. CaSiO 3 doses (0.5, 1 and 2 mmol•L-1) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…In addition, reports have shown that Si treatment results in short-term accumulation of phenolics followed by a subsequent decline, signalling Si formulation-induced mitigation of salt stress effect, and hence stress alleviation [75,103]. In line with our findings, studies have also reported a Si-mitigated decline in the content of phenolics in salt-stressed apples and Jatropha integerrima, respectively [104,105]. In conclusion, application of Si-based formulations on salt-stressed plants confers higher tolerance thereof via accumulation of phenolics which, in turn, activate defence-related proteins, repair and regulate photosynthetic apparatus, scavenge ROS, inhibit ROS-producing enzymes as well as activate antioxidant enzymes.…”
Section: Si-based Biostimulant Altered Secondary Metabolism Towards the Salt-stress Alleviation In Tomato Plantssupporting
confidence: 91%
“…In addition, reports have shown that Si treatment results in short-term accumulation of phenolics followed by a subsequent decline, signalling Si formulation-induced mitigation of salt stress effect, and hence stress alleviation [75,103]. In line with our findings, studies have also reported a Si-mitigated decline in the content of phenolics in salt-stressed apples and Jatropha integerrima, respectively [104,105]. In conclusion, application of Si-based formulations on salt-stressed plants confers higher tolerance thereof via accumulation of phenolics which, in turn, activate defence-related proteins, repair and regulate photosynthetic apparatus, scavenge ROS, inhibit ROS-producing enzymes as well as activate antioxidant enzymes.…”
Section: Si-based Biostimulant Altered Secondary Metabolism Towards the Salt-stress Alleviation In Tomato Plantssupporting
confidence: 91%
“…The severity of salt stress progressively enhanced the EL and the tolerance rate of plants against salt stress [ 74 ]. Exogenously applied Si protects plants from salt induced membrane damage [ 75 ]. Silicon fertilizer also provides strength to the cell membrane of those plants which grow under salt stress [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exogenously applied Si protects plants from salt induced membrane damage [ 75 ]. Silicon fertilizer also provides strength to the cell membrane of those plants which grow under salt stress [ 75 , 76 ]. The addition of Si fertilizer in saline soils shows the reduction in electrolytic leakage hence preventing ion leakage from the plasma membrane and a decrease in lipid peroxidation [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Si may induce internal Fe and Mg transport, leading to the synthesis of chlorophyll. Similarly, as with the chlorophyll content, the Si treatment increased the chlorophyll stability index as reported by (Aras et al, 2020).…”
Section: Effect Of Salinity Stress On Seed Yield and Biological Yieldsupporting
confidence: 59%